ZAMANAGÓY KIYIMLERDE KESTESHILIK ÓNERIN QOLLANIW TEXNOLOGIYASĺ - Berdimbetova, A. (SCIENCE and SOCIETY, 2023)
The article states the art of decorating fabric with national embroidery arose in ancient times as a result of people's desire to decorate their lives. Information is given about the ways of decorating clothes on the basis of modern nationality, passing it on to future generations while preserving the nationality, embroidery methods.